Integrasi Gastronomi Gizi, Nilai Budaya, dan Penguatan UMKM pada Dali Ni Horbo sebagai Pangan Fungsional dan Wisata Berkelanjutan - nisaul zahra; Riski Ainaul Mardiyah; Tiara Nauli Panggabean; Lyndon Fredli Lubis; Esi Emilia; Jenri P Hutasoit; Reny Yuliana Siahaan (Jurnal Sains Boga, 2026)
Dali Ni Horbo, a traditional Batak food from buffalo milk, is a unique gastronomic product with a soft texture resembling tofu or cheese, savory umami flavor, and natural coagulation using aloe vera. This study employs a qualitative descriptive approach conducted in Samosir Island, North Sumatra, involving UMKM actors, adat leaders, local communities, and tourists as informants. Data collection techniques include in- depth interviews, observation, and documentation, analyzed using an interactive qualitative model. Findings reveal that Dali Ni Horbo has a soft texture, savory taste, and traditional processing. The product reflects cultural values, high nutrition, and potential as a functional food and gastronomic tourism asset, though it requires innovation and promotion. Thus, Dali Ni Horbo plays a role in enhancing nutrition, cultural preservation, UMKM strengthening, and sustainable tourism.